Stability problems in hyperinflation models - Helmut Zink (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1993)
Traditional monetary models of hyperinflation suffer from severe stability problems: equilibria with realistic comparative-static properties are unstable while those with unrealistic comparative statics are stable. In the present paper I develop a model of hyperinflation which is based on an analysis of firms' payment behavior and which uses a weaker concept of stability. The stability properties of this model are consistent with the empirical evidence.
Keywords: E31; C62; 330; Monetary theory; hyperinflation; stability